Postpartum heavy episodic drinking: A survey to inform development of a text messaging intervention. (30th June 2021) - Dauber, Sarah; West, Allison; Hammond, Cori; Cohen, Ilana; Thrul, Johannes
Abstract: Introduction: Text messaging interventions (TMI) are promising for addressing heavy episodic drinking (HED) in non‐treatment‐seeking postpartum women. Their anonymous delivery can overcome fear of consequences that often prevents postpartum women from seeking treatment for HED. We assessed feasibility and acceptability of text messaging to inform the development of a tailored TMI for postpartum HED. Methods: We surveyed 165 postpartum women recruited via a national Qualtrics panel on their drinking behaviours, mobile technology use and TMI preferences. Results: Twenty‐five percent of the sample ( N  = 41) were classified as heavy episodic drinkers, with significant drinking reported before, during and after pregnancy, supporting the need for intervention. Feasibility of text messaging was supported by nearly universal mobile phone ownership and text messaging. Attitudes and intervention preferences varied, with 30% of HEDs likely to participate in an intervention asking them to receive automated messages, and 46% likely to participate in an intervention that included live texting with a counsellor. Respondents were more likely to participate in a study that asked them to respond to messages about mood and stress (63%) than daily drinking behaviours (35%), and were most interested in a TMI that included live texting with a counsellor. Nearly half the sample endorsed fear of child removal as a significant barrier to participation. Discussion and Conclusions: Findings support the feasibility of text messaging as an intervention approach for postpartum HEDs. Postpartum women may have unique concerns and preferences that differ from other groups of HEDs, making a user‐centred design approach critical.